Kecerdasan Matematis dan Penguatan Literasi Matematika pada Siswa Sekolah Dasar - Nurhaswinda Nurhaswinda (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Mathematical intelligence is the ability to understand and solve mathematical problems and relate mathematical concepts to everyday life. In elementary school, students' mathematical intelligence needs to be developed through strengthening mathematical literacy, which includes the ability to read, write, and solve mathematical problems critically. This literature study aims to analyze various approaches and strategies that can strengthen mathematical intelligence and mathematical literacy in elementary school students. The method used in this study is a literature study by reviewing articles and related research in the last five years regarding mathematics learning, mathematical literacy, and mathematical intelligence. The results of the study indicate that problem-based learning approaches, the use of digital technology, and collaborative learning can improve students' understanding of mathematical concepts and their ability to solve mathematical problems effectively. In addition, strengthening mathematical literacy through contextual learning that is relevant to everyday life has been shown to increase students' interest and understanding. This study recommends the need for integration of mathematical literacy in the elementary school mathematics curriculum and the development of teacher competence in using various innovative and technology-based learning approaches.